IMPLEMENTASI PELAJAR PANCASILA BERNALAR KRITIS SISWA PADA PEMBELAJARAN IPAS DI KELAS IV - Arifin, Zaenal; Miftachudin, Miftachudin; Muttaqin, Muhammad Fauzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research aims to analyze the implementation of Pancasila students' critical reasoning in science learning in class IV elementary school. The method used is qualitative with a descriptive model. Research subjects Principal, class IV teacher, class IV students at SD Daarul Quran Tangerang. Data collection uses observation, interviews and document study. The data validation process uses triangulation techniques. Data analysis uses interactive analysis consisting of data collection, reduction, data display, and conclusions. The research results show that the implementation of critical reasoning from the Pancasila Student Profile in science and science learning in class IV elementary schools shows positive results. Application of Critical Reasoning in Natural Sciences Learning through learning strategies, use of learning media, active role of teachers as facilitators and feedback, thereby creating enthusiasm and participation in students developing critical thinking skills. There are obstacles including limited time and variations in student abilities. The implications of this research provide valuable insights for educators and policy makers to continue developing and implementing critical reasoning elements from the Pancasila Student Profile in the basic education curriculum.